Miniaturized cardiopulmonary bypass: the Hammersmith technique - Momin, Aziz (BioMed Central, 2013)
BACKGROUND: Conventional Cardiopulmonary Bypass (cCPB) is a trigger of systemic inflammatory reactions, hemodilution, coagulopathy, and organ failure. Miniaturised Cardiopulmonary Bypass (mCPB) has the potential to reduce these deleterious effects. Here, we describe our standardised ‘Hammersmith’ mCPB technique, used in all types of adult cardiac operations including major aortic surgery. METHODS: The use of mCPB remains limited by the diversity of technologies which range from extremely complex, micro systems to ones very similar to cCPB. Our approach is designed around the principle of balancing the benefits of miniaturisation; reducing foreign surface area while maintaining patient safety. RESULTS: From January 2010 to March 2011, a single surgeon performed 184 consecutive operations (Euro score Logistic 8.4+/-9.9): 61 aortic valve replacements, 78 CABGs, 25 aortic valve replacement and CABG and 17 other procedures (major aortic surgery, re-do operations or double/triple valve replacements). Our clinical experience suggests that: i. Venous drainage is optimally maintained using kinetic energy. ii. Venous collapse pressure depends on the patient’s anatomy and cannula size, but most importantly on the negative pressure generated by venous drainage. iii. The patient-prime interaction is optimised with antegrade and retrograde autologous priming, which mixes the blood and prime away from the tissues and results in a reduced oncotic destabilization. iv. mCPB is a safe and reproducible technique CONCLUSION: The Hammersmith mCPB is a “next generation” system which uses standard commercially available components. It aims to maintain safety margin and the benefit of miniaturised system whilst reducing the human factor demands.